Hubungan Pola Makan Dengan Kekambuhan Gastritis Pada Masyarakat di Wilayah Kerja Pustu Mantimin - Herliyanti, Herliyanti; harun, lukman; Suwandewi, Alit (Journal of Nursing Invention, 2023)
Background : Irregular eating patterns will make it difficult for the stomach to adapt. If this continues for a long time, excess stomach acid will be produced which can irritate the stomach walls. Based on medical journals, 40% of gastritis sufferers are caused by stress due to work problems, household problems, irregular eating patterns, which causes frequent recurrences of gastritis. Gastritis complications are bleeding, pernicious anemia, and stomach cancer Objective: This research was to determine the relationship between diet and recurrence of gastritis in the community in the Pustu Mantimin work area Method: This research uses a quantitative research type of correlation study with a cross sectional approach, namely research to study the relationship between two variables, where all the variables observed are measured while the research is taking place. The independent variable is diet and the dependent variable is the occurrence of gastritis recurrence. Result: The results of the research show that there is a relationship between diet and recurrence of gastritis in the community in the Pustu Mantimin Working Area with a calculated Chi Square value of 5,719 Chi Square Table 43,775 with a sig level result of 0.022 < 0.05. then it can be concluded that Ha is accepted and Ho is rejected. This means that there is a relationship between diet and recurrence of gastritis in the community in the Pustu Mantimin Working Area. In the risk estimate for recurrence of gastritis, the odds ratio (OR) value in this study was 150, which means an evaluation of the relationship between diet and recurrence of gastritis. Conclusion: There is a relationship between diet and recurrence of gastritis in the community in the Pustu Mantimin Working Area